Applying Gamification in BINUS University Library and Knowledge Center - Monika Yulinda Harahap, Mario Saputra Lienarto, Emil R. Kaburuan, Gunawan Wang (International Journal of Control and Automation, 2020)
Gamification is a well-known concept for applying game elements in non-gaming environments. Gamifications has been adopted in several industries in order to improve the organizations. This paper focuses on gamifications in education sectors. Education is one of the sectors that has potential to benefit from gamification. There have been obstacles for Indonesia when it comes to the education system. On the national level, Indonesia is lagging behind developed countries and substantial endeavor is needed in order to make up for the lost time. On university level, there is a tendency for students to lose or damage books, late return of books that are overdue, and difficulty to keep noises below acceptable levels. Another difficulty that BINUS is currently facing is ensuring the availability of books to accommodate students’ needs. This paper proposes gamification concepts for BINUS University Library and Knowledge Center to overcome all limitations mentioned above. The proposed gamifications concept can be viewed as a pilot project that can be conducted in BINUS university. If the concept is proven to be successful, more than higher education institutions can start adopting the gamification concepts with adjustments corresponding to their requirements and policy.